Disapperance of the pond at Furmanów (Old-Polish Industrial District) - Fularczyk, Karolina; Kalicki, Tomasz (Acta Geographica Lodziensia, 2021)
The research area lies within the Old-Polish Industrial District (OPID), which functioned in recent centuries, where appropriate environmental conditions such as shallow ironore deposits, high forest cover and the availability of hydropower supplied by rivers contributed to the development of mining and metallurgy. This activity led to changes in valley floors and the river n-twork that are visible on historical and contemporary cartographic materials, as well as in the relief and sediments of different origins. This work is a case study of a former waterbody at Furmanów in the Czarna Konecka River valley (Małopolska Upland), where the preliminary analysis of cartographic materials allowed to select the object for detailed research.